2021
DOI: 10.1093/function/zqab004
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarettes and Cardiopulmonary Health

Abstract: E-cigarettes have surged in popularity over the last few years, particularly among youth and young adults. These battery-powered devices aerosolize e-liquids, comprised of propylene glycol (PG) and vegetable glycerin (VG), typically with nicotine, flavors and stabilizers/humectants. Although the use of combustible cigarettes is associated with several adverse health effects including multiple pulmonary and cardiovascular diseases, the effects of e-cigarettes on both short- and long-term health have only begun … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 165 publications
0
38
0
1
Order By: Relevance
“…Pre‐clinical studies with e‐cigarette aerosols, flavor chemicals and nicotine show a variety of toxic effects including cytotoxicity, altered vascular function, inflammation and platelet activation that could contribute to CVD [51]. However, it is difficult to extrapolate preclinical studies to human disease risk owing to differences in doses and exposure schedules and the model test system.…”
Section: Cardiovascular Disease Risk From Tobacco Products Other Than...mentioning
confidence: 99%
“…Pre‐clinical studies with e‐cigarette aerosols, flavor chemicals and nicotine show a variety of toxic effects including cytotoxicity, altered vascular function, inflammation and platelet activation that could contribute to CVD [51]. However, it is difficult to extrapolate preclinical studies to human disease risk owing to differences in doses and exposure schedules and the model test system.…”
Section: Cardiovascular Disease Risk From Tobacco Products Other Than...mentioning
confidence: 99%
“…Emerging data indicate that e-cig use may adversely affect the pulmonary and cardiovascular systems [24,[35][36][37][38][39]. Also, limited evidence exists on the potential of e-cigs to cause carcinogenic effects [32,33,[40][41][42][43][44][45].…”
Section: Health Consequences: Smoking Vs Vapingmentioning
confidence: 99%
“…Despite increasing popularity of electronic cigarettes (e-cigarettes), the long-term health effects of habitual e-cigarette use remain unclear. 1 Many constituents of e-cigarette aerosols, including nicotine, carbonyl compounds, fine particulate matter, and metals, are associated with substantial toxicity. 1 Inhalation of e-cigarette aerosols among young, healthy adults induces inflammation and oxidative stress.…”
mentioning
confidence: 99%
“…1 Many constituents of e-cigarette aerosols, including nicotine, carbonyl compounds, fine particulate matter, and metals, are associated with substantial toxicity. 1 Inhalation of e-cigarette aerosols among young, healthy adults induces inflammation and oxidative stress. 1 Two large cross-sectional studies reported no significant association between exclusive e-cigarette use and cardiovascular disease (CVD).…”
mentioning
confidence: 99%
See 1 more Smart Citation